2006
DOI: 10.1097/01.ajp.0000210997.53082.c9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Head and Neck Position Have a Greater Effect on Elbow Joint Position Sense in People With Whiplash-associated Disorders

Abstract: Elbow JPE is affected by movement of the head and neck, with smaller angles of neck rotation in people with WAD than in healthy individuals. This observation may explain deficits in upper limb coordination in people with WAD, which may be due to the presence of pain or reduced range of motion in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 22 publications
3
54
0
Order By: Relevance
“…Similar findings of impaired upper limb Knox, Beilstein, et al, 2006) and head repositioning accuracy have been documented in individuals with clinical neck pain when compared to controls Sjölander, Michaelson, Jaric, & Djupsjöbacka, 2008). In addition, individuals suffering neck pain of both traumatic, and insidious onset, have been shown to exhibit impaired performance of smooth pursuit and saccadic eye movement tests in comparison to asymptomatic controls (Gimse, Tjell, Bjôrgen, & Saunte, 1996;Treleaven, 2008b;Uthaikhup et al, 2012).…”
Section: Pain-induced Impairment Of Proprioceptive Functionsupporting
confidence: 64%
“…Similar findings of impaired upper limb Knox, Beilstein, et al, 2006) and head repositioning accuracy have been documented in individuals with clinical neck pain when compared to controls Sjölander, Michaelson, Jaric, & Djupsjöbacka, 2008). In addition, individuals suffering neck pain of both traumatic, and insidious onset, have been shown to exhibit impaired performance of smooth pursuit and saccadic eye movement tests in comparison to asymptomatic controls (Gimse, Tjell, Bjôrgen, & Saunte, 1996;Treleaven, 2008b;Uthaikhup et al, 2012).…”
Section: Pain-induced Impairment Of Proprioceptive Functionsupporting
confidence: 64%
“…12 Interestingly, position sense deficits have not been isolated to the neck in this population, with deficits also seen in the shoulder and elbow in some patients with traumatic neck pain. 57,91 Cervical Movement Accuracy Several studies have looked at accuracy of fine motion control in the neck of those with traumatic neck pain as another measure of proprioception. Kristjansson [ clinical commentary ] demonstrated less accuracy in tracing a computer-generated movement pattern with the head in those with traumatic neck pain when compared to both a control group and individuals with INP.…”
Section: Cervical Proprioceptionmentioning
confidence: 99%
“…20 They argued that placing their participants' heads in full flexion and rotation could have led to an overload of the computational capacity of the CNS, thus resulting in increased JPS error. 20 The same group of researchers also demonstrated that people with whiplash-associated disorder (WAD) are affected by smaller angles of neck rotation than individuals who had no history of WAD, 21 further suggesting that cervical spine dysfunction leads to reduced accuracy of JPS. Taken together, these studies suggest that spinal function can impact central proprioceptive processing not only of the spine itself, as the study of Palmgren et al 19 suggests, but also of the upper limb.…”
mentioning
confidence: 99%